Implementation of the Musyarakah Mutanaqishah Contract on KPR Platinum BTN iB: A Case Study at the Depok Sharia Branch Office - Anwar, Kholid (SIGn Journal of Social Science, 2025)
Although administratively appearing compliant, this research reveals a tension between formal compliance and empirical reality in the implementation of the MMQ contract, particularly in responding to developer marketing strategies, such as the 0% DP scheme. This study aims to analyze the administrative construction of the contract to accommodate developer promos, evaluate the validity of hishshah formation, and critique the legal implications of early asset ownership transfers. The research method employs a juridical-empirical approach through a case study at the BTN Sharia Depok Branch Office, using triangulation data collection techniques consisting of in-depth interviews, system observation, and critical document review of Financing Approval Letters and Financing Contracts. The results indicate a fundamental distortion in which the “mandatory paid-off receipt” administrative mechanism is used as a formal legitimation tool to bridge the gap between the bank’s Standard Operating Procedures requiring a down payment and the developer’s marketing strategy (gimmick) that eliminates it. This condition causes a legal defect in hishshah formation due to the violation of the cash capital requirement in syirkah, and creates unfair risk distribution consequent to the certificate title transfer practice and aggressive collateral execution clauses. This study concludes that the administrative response to such developer promos can shift contract substance to full debt financing wrapped in a partnership label, thereby recommending stricter technical regulations from relevant authorities to filter third-party promotion schemes incompatible with contract principles.